Explicit versus implicit food subsidies: Distribution of costs - Valdés, Alberto (International Food Policy Research Institute, 1988)
For years economists have tried to go beyond the strictly economic "efficiency" measure of costs and benefits to resolve the problem of how to explicitly incorporate some of the noneconomic benefits and costs into their analytical framework.1 One of the major issues is assigning weights to consumption gains accruing to different income groups, especially the consumption of food by the poor and malnourished. These noneconomic considerations are difficult to quantify, particularly when there is no consensus about the underlying noneconomic values.